The Influence of Organizational Culture, Commitment, and Leadership on Employee Job Satisfaction at PT. Abadi Harmoni Mulia - Hendry Hendry; Felix Hartanto; Edwina Suwandi Salim; Windy Fortuna; Adria Wuri Lastari (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this study was to determine and evaluate the influence of organizational culture, commitment, and leadership, partially and simultaneously, on employee job satisfaction at PT Abadi Harmoni Mulia. This study uses a quantitative descriptive method. In 2022, the study population was 36 employees of PT Abadi Harmoni Mulia. We sampled 36 people for this study using a saturated sampling approach. We used multiple linear regression as a statistical technique for analysis. The final result of this study is that organizational culture, commitment, and leadership have a partial and simultaneous effect on employee job satisfaction at PT. Abadi Harmoni Mulia.